Beyond The Smoke: Historical and Ethnographic Notes on The Dayak Basap - Manarul Hidayat (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
This article explores the social history and ethnographic realities of the Dayak Basap, an indigenous people group in East Kalimantan, Indonesia, whose presence remains underrepresented in anthropological literature. Drawing on 47 days of fieldwork conducted in 2022 across several villages in Karangan Subdistrict, especially Karangan Seberang Village, the study examines processes of ethnogenesis and ethnic distribution, intersocietal relations, migration pathways, and cultural continuity. It challenges outsider interpretations of the term "Basap" as “smoke people,” reframing it through emic perspectives that assert territorial primacy and ancestral rootedness. The article integrates prior scholarly works with original ethnographic data, documenting social structure and kinship systems, language and necronymic naming, customary law and fines, livelihood and daily subsistence, and shamanistic beliefs. By analyzing both historical structures of subordination under the Kutai Sultanate and contemporary dynamics of marginalization, the article presents the Dayak Basap as a culturally resilient community navigating ecological, political, and spiritual transformations.